2005
DOI: 10.2355/isijinternational.45.414
|View full text |Cite
|
Sign up to set email alerts
|

Summarized Achievements of the Porous Meso-mosaic Texture Sinter Research Project

Abstract: Research Group on Porous Meso-mosaic Texture Sinter in ISIJ was established from 2001 to 2004 fiscal years to overcome difficulties to use the great amount of goethite in sintering and at the same time to improve the sinter quality. Especially, since the beginning of the present research project the ratio of Marra Mamba goethitic ore was considered to increase rapidly, and the amount of sinter necessary for the Japanese integrated steel industries was thought hard to be produced satisfactorily, because Marra M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Recently in the research project on "Sintering through Designing of Composite Granulation & Bed Structure" undertaken by a group led by Kasai, MEBIOS (mosaic embedding iron ore sintering) [7][8][9] is under study. The main objectives of the MEBIOS sintering method are to find measures for the effective utilization of Marramamba iron ore and measures to improve sinter productivity, and by embedding pellets made mainly of Marramamba iron ore, ventilation routes are effectively formed in the sintering structure, improving the productivity of sinter.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in the research project on "Sintering through Designing of Composite Granulation & Bed Structure" undertaken by a group led by Kasai, MEBIOS (mosaic embedding iron ore sintering) [7][8][9] is under study. The main objectives of the MEBIOS sintering method are to find measures for the effective utilization of Marramamba iron ore and measures to improve sinter productivity, and by embedding pellets made mainly of Marramamba iron ore, ventilation routes are effectively formed in the sintering structure, improving the productivity of sinter.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the strength, reducibility and size distribution of sinter particles and the yield from a sinter strand are determined by the inherent strength of the bonding phases present and the structure of the pores. 22,23) Furthermore, different pore sizes seem to have different effects on sinter strength, reducibility and other properties: the high temperature reducing property is controlled by the micro-pore sinter structure, while the sinter strength is determined by the macro-pore sinter structure. 22,23) It is therefore important to optimise the pore structure in sinter to improve its reducibility, while maintaining the cold strength, reduction degradation and load softening properties.…”
mentioning
confidence: 99%
“…22,23) Furthermore, different pore sizes seem to have different effects on sinter strength, reducibility and other properties: the high temperature reducing property is controlled by the micro-pore sinter structure, while the sinter strength is determined by the macro-pore sinter structure. 22,23) It is therefore important to optimise the pore structure in sinter to improve its reducibility, while maintaining the cold strength, reduction degradation and load softening properties.The physicochemical properties of the primary melt become increasingly important as the amount of slag in sinter decreases. Loo and Leung discussed the effect of the physicochemical properties of the primary melt on the reshaping and coalescing process of the primary melt and bubbles formed in the flame front during sintering and therefore on the resulting pore structure of the sinter.…”
mentioning
confidence: 99%
“…[18][19][20] Similar process named mosaic embedding iron ore sintering (MEBIOS) displays its predominance on efficiently using low-grade iron ores and limonite, ensuring high productivity and reducibility and enhancing sinter strength. [21][22][23] Our previous study 24) showed that acidic sinter (basicity < 0.5) made from titanomagntite concentrate mainly solidifies in the form of titanohematite and titanomagnetite and very few perovskite was generated in this sinter. Ultra-high basicity (basicity > 2.5) facilitated the formation of SFCA in sinter, which can offset the adverse effect of perovskite to sinter strength due to its excellent bonding strength.…”
Section: Preparation Of Bf Burden From Titanomagnetite Concentrate Bymentioning
confidence: 99%